Książę Mastema i jego armia w Księdze Jubileuszy - Tronina, Antoni (The Biblical Annals, 2024)
The Book of Jubilees is a valuable testimony of the “intertestamental” literature from the time of the Maccabean struggles for the religious and national sovereignty of Israel. The topic under discussion concerns the term which describes the leader of the evil spirits as “Prince Mastema.” “Mastema” is not so much a personal name, but rather a designation of function in the world. The term “Lord of Hostility” is not presented here as an opponent of God, but rather as the commander of an army of evil spirits that will wage war against God-faithful spirits in the end times.